2020
DOI: 10.1155/2020/4048706
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Yeast Alleviates Ochratoxin A-Induced Apoptosis and Oxidative Stress via Modulation of the PI3K/AKT and Nrf2/Keap1 Signaling Pathways in the Kidneys of Chickens

Abstract: The purpose of this study was to investigate the protective effect and mechanism of yeast selenium (Se-Y) on ochratoxin- (OTA-) induced nephrotoxicity of chickens. A total of 80 one-day-old healthy chickens were randomly divided into 4 equal groups: control, OTA (50 μg/kg OTA), Se-Y (0.4 mg/kg Se-Y), and OTA+Se-Y (50 μg/kg OTA+0.4 mg/kg Se-Y). In the OTA chickens, differences in body weight, kidney coefficient, biochemical histological analysis, antioxidant capability, and the expression levels of the PI3K/AKT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 61 publications
4
23
0
Order By: Relevance
“…TNF-α, an inflammatory cytokine belonging to tumor necrosis factor/ tumor necrosis factor receptor (TNF/TNFR) cytokine superfamily, plays key role in biological functions, such as the maintenance of homeostatic balance and immune function, and resistance capacity to infection and cancers ( 59 ). Previous reports showed that dietary Se plays a protective role against aflatoxin B 1 and ochratoxin A-induced inflammation and apoptosis in liver and kidney ( 60 , 61 ). In this work, TNF-α expression in oviduct tissue of laying hens was significantly higher in SEIP group compared with SEY group.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α, an inflammatory cytokine belonging to tumor necrosis factor/ tumor necrosis factor receptor (TNF/TNFR) cytokine superfamily, plays key role in biological functions, such as the maintenance of homeostatic balance and immune function, and resistance capacity to infection and cancers ( 59 ). Previous reports showed that dietary Se plays a protective role against aflatoxin B 1 and ochratoxin A-induced inflammation and apoptosis in liver and kidney ( 60 , 61 ). In this work, TNF-α expression in oviduct tissue of laying hens was significantly higher in SEIP group compared with SEY group.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Eraslan et al [ 55 ] reported that exposure to AF at high doses caused lipid peroxidation in broilers. Li et al [ 56 ] reported the effect of adding OTA in the diet of broilers in the inclusion rate of 50 μg/kg. MDA levels in kidneys were increased while the total antioxidant capacity (TAC) was decreased and levels of SOD, CAT, and GSH were markedly lower than in the control group.…”
Section: The Effect Of Mycotoxins On the Antioxidant Status Of Pigmentioning
confidence: 99%
“…The decrease in Nrf2 activation induced by OTA was also observed in NRK-52E rat kidney cells were the influence of another oxidative stress regulator was suggested: hypoxia inducible factor 1α (HIF-1α) which activation was associated with angiogenesis (Liu et al 2020). Induction of apoptosis and oxidative stress by OTA in chicken kidneys and liver was associated with modulation of Nrf2/Keap1 as well as PI3K/Akt signalling pathways as confirmed by Li et al (2020a). The decreasing expression of Nrf2 and HO-1 was also observed after treatment of porcine renal proximal tubular cells with OTA (Stachurska et al 2013).…”
Section: Ochratoxin Amentioning
confidence: 68%